2017
DOI: 10.3892/ol.2017.5923
|View full text |Cite
|
Sign up to set email alerts
|

Andrographolide induces apoptotic and non-apoptotic death and enhances tumor necrosis factor-related apoptosis-inducing ligand-mediated apoptosis in gastric cancer cells

Abstract: Abstract. Andrographolide, a natural compound isolated from Andrographis paniculata, has been reported to possess antitumor activity. In the present study, the effect of andrographolide in human gastric cancer (GC) cells was investigated. Andrographolide induced cell death with apoptotic and non-apoptotic features. At a low concentration, andrographolide potentiated apoptosis and reduction of clonogenicity triggered by recombinant human tumor necrosis factor-related apoptosis-inducing ligand (rhTRAIL). Exposur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 37 publications
3
22
0
Order By: Relevance
“…This result is supported by previous studies that poncirin and tangeretin also induced apoptosis through the death receptor-mediated apoptotic pathway [51,52]. Other studies have reported similar results that show that the molecular mechanisms of apoptosis in gastric cancer cells are related to DR4 [53] and DR5 [54]. These data support the hypothesis that the regulation of DR4 and DR5 is a key molecular mechanism underlying apoptosis in AGS cells.…”
Section: Discussionsupporting
confidence: 89%
“…This result is supported by previous studies that poncirin and tangeretin also induced apoptosis through the death receptor-mediated apoptotic pathway [51,52]. Other studies have reported similar results that show that the molecular mechanisms of apoptosis in gastric cancer cells are related to DR4 [53] and DR5 [54]. These data support the hypothesis that the regulation of DR4 and DR5 is a key molecular mechanism underlying apoptosis in AGS cells.…”
Section: Discussionsupporting
confidence: 89%
“…It remains controversial whether DR4 or DR5 represents the determinant receptor associated with TRAIL-induced apoptosis. Previous studies claimed that DR4 was more effective in promoting TRAIL-mediated cancer-cell apoptosis 28-30; whereas other studies indicated DR5 was critical for promoting TRAIL-induced cancer-cell apoptosis 25. Here, by using siRNA targeting DR4 or DR5, we confirmed that both DR4 and DR5 were required for tumor suppressing activity by combined treatment with Andro and TRAIL in BLCA cells.…”
Section: Discussionsupporting
confidence: 71%
“…Thus, novel treatments are required to improve the outcomes of patients with osteosarcoma. Andrographolide has been reported to be a promising therapeutic for treatment of multiple types of cancer, with potent antitumor effects and minimal toxicity (11,29,(39)(40)(41)(42). However, little is known about the effects and biochemical mechanisms of action of andrographolide in osteosarcoma.…”
Section: Discussionmentioning
confidence: 99%
“…The detailed mechanisms responsible for the antitumor effects of andrographolide remain uncertain. It has been shown that andrographolide can induce cytotoxicity and cell cycle arrest in breast cancer, prostate cancer, laryngeal cancer and gastric cancer by upregulating ROS production, leading to programmed cell death (27)(28)(29)(30). Andrographolide has also been found to induce human hepatoma cell death through JNK activation (31).…”
Section: Introductionmentioning
confidence: 99%